Glycosylation of H4 influenza strains with pandemic potential and susceptibilities to lung surfactant SP-D - Parsons, Lisa M.; Zoueva, Olga; Grubbs, Gabrielle; Plant, Ewan; Jankowska, Ewa; Xie, Yijia; Song, Hao; Gao, George F.; Ye, Zhiping; Khurana, Surender; Cipollo, John F. (Frontiers in Molecular Biosciences, 2023)
We recently reported that members of group 1 influenza A virus (IAV) containing H2, H5, H6, and H11 hemagglutinins (HAs) are resistant to lung surfactant protein D (SP-D). H3 viruses, members of group 2 IAV, have high affinity for SP-D, which depends on the presence of high-mannose glycans at glycosite N165 on the head of HA. The low affinity of SP-D for the group 1 viruses is due to the presence of complex glycans at an analogous glycosite on the head of HA, and replacement with high-mannose glycan at this site evoked strong interaction with SP-D. Thus, if members of group 1 IAV were to make the zoonotic leap to humans, the pathogenicity of such strains could be problematic since SP-D, as a first-line innate immunity factor in respiratory tissues, could be ineffective as demonstrated in vitro. Here, we extend these studies to group 2 H4 viruses that are representative of those with specificity for avian or swine sialyl receptors, i.e., those with receptor-binding sites with either Q226 and G228 for avian or recent Q226L and G228S mutations that facilitate swine receptor specificity. The latter have increased pathogenicity potential in humans due to a switch from avian sialylα2,3 to sialylα2,6 glycan receptor preference. A better understanding of the potential action of SP-D against these strains will provide important information regarding the pandemic risk of such strains. Our glycomics and in vitro analyses of four H4 HAs reveal SP-D-favorable glycosylation patterns. Therefore, susceptibilities to this first-line innate immunity defense respiratory surfactant against such H4 viruses are high and align with H3 HA glycosylation.